Impact of bedside diagnosis of influenza in the paediatric emergency ward. (July 2019) - Cantais, A.; Mory, O.; Plat, A.; Bourmaud, A.; Giraud, A.; Costille, M.; Pozzetto, B.; Pillet, S.
Abstract: Objectives: This prospective study performed in the paediatric emergency department of the University Hospital of Saint-Etienne aimed to measure the impact of the 24/7 bedside use of the Veritor™ System (Becton Dickinson) on the reduction of supplementary investigations, hospital stay and antimicrobial use. Methods: Influenza virus A and B antigens were detected with a rapid influenza digital immunoassay (DIA) on nasopharyngeal aspirates (NPAs) sampled from the children consulting at the paediatric emergency department between January and March 2016 for influenza-like illness. The same NPA was tested by immunofluorescence and/or molecular routine assays. Before performing the DIA, the clinician filled in a questionnaire listing the tests that he/she would have prescribed in the absence of the rapid testing. The prescription of complementary investigations, antimicrobial treatments and hospital stay were also compared to those of the 3 previous years. Results: A total of 514 children with flu-like symptoms were included. The use of the DIA at bedside decreased the prescription of blood puncture by 47.9% (21.2% to 6.6%), of chest X-rays by 69.0% (33.3% to 10.3%), of lumbar puncture by 77.8% (7.0% to 1.6%), of urine culture by 79.2% (23.3% to 4.9%), of antibiotic treatments by 70.1% (16.9% to 5.1%), and of hospital stay by 25.0% (27.2% to 20.4%), resulting in a reduction of medical costs estimated to more than €69 000 in a season. Conclusions: In addition to delivering a rapid aetiological diagnosis, this strategy saves medical costs and favours an antimicrobial stewardship strategy. However, further prospective studies are needed to confirm our findings.